Evolução da mineração na Amazônia Oriental brasileira:aspectos políticos, econômicos, sociais e ambientais - SEBAJE, Alexandre de Ramos (2019)
The presented work of monograph however develops an analysis concerning the processes of the structural and conjunctural development of the economic sector that involves the activity of the enterprise mining in the Brazilian Eastern Amazônia. In this work the description of the historical process of this development was carried through, considering itself it its relation in terms of impacts caused on half the social physicist and, involving the contexts, economic, politician, social and ambient, from the executed projects of mining and in execution in the states of the Amapá and Pará over all, in the regions of entorno of the respective cited and used projects as object of the developed analyses. The research work presents as conclusion the hypothesis of the occurrence of the called phenomena of the curse of the resources and of the dutch illness in the context of the mineral industry in the region of the Brazilian Eastern Amazônia. Such phenomena of partner-economic nature had been used as referencial theoretician in elapsing of the process of evaluation of the results generated in the time and the space for the Amazonian industrial mining.